Analisis Diskriminan Kompetensi Profesional Guru Sekolah Dasar Islam Terpadu : Discriminant Analysis of Professional Competency of Integrated Islamic Elementary School Teachers - Alhan, Khusni; Gustaman, Agung; Waeno, Mahamadaree (STAI Publisistik Thawalib Jakarta, 2024)
The purpose of this study was to determine the factors that differentiate teachers' competencies. This research used a quantitative method with a survey approach. The population of this study was 99 teachers from Nurul Iman Integrated Islamic Elementary School and Al-Azhar Jaka Permai Islamic Elementary School. The statistical analysis used was multiple regression analysis and residual test for moderating variables. The results showed that there are 4 variables that significantly (p = 0.05) can demonstrate differences in teachers' professional competencies, namely: interactivity and mastery of student development are the most dominant variables that can identify differences in teacher competencies, as seen in the canonical correlation coefficient of 0.609, which when squared becomes (0.609)² = 0.370, meaning that 37% of the variation in teacher professional competency variables is explained by discriminant variables, namely interactive and understanding student development variables that can identify differences in teacher competencies through the test (Wilk’s Lambda = 0.629; Chi-square = 11.360 and p = 0.000); Discriminant function equation: Z = -.002 + 0.379 X3.2 - 0.240 X4.2.